Exploring the Link Between Oxidative Stress Reduction and Liver Function Improvement in Jaundiced Rats with Lactococcus lactis D4 - Avit Su Suchitra (Faculty of Medicine, Universitas Andalas, 2024)
Objective: To explore the correlation between the reduction of oxidative stress and liver enzyme function in rats with obstructive jaundice, using malondialdehyde (MDA) levels as a biochemical marker, and its impact on serum glutamic oxaloacetic transaminase (SGOT) levels; Method: This experimental study used a post-test only randomized control group design in three groups of Rattus norvegicus strain Wistar rats with an obstructive jaundice model. The rats underwent biliary duct ligation and received Lactococcus lactis D4 starter fermented milk for 7 days. Oxidative stress was assessed by measuring MDA levels and Liver function was assessed by measuring levels of SGOT ; Result: The correlation analysis show an r-value of 0.886 revealed that there a very strong positive correlation between MDA and SGOT levels after LLD4 administration; Conclusion: Lactococcus lactis D4 starter fermented milk can improve liver function, indicated by decreased MDA levels and SGOT levels in experimental animals.